SPATIAL AND TEMPORAL DYNAMICS OF LAND USE AND FIRE HOTSPOTS IN THE MUNICIPALITY OF MIRANDA-MS - Leite, Emerson Figueiredo; Carvalho, Elisângela Martins de; Farias, Fernando Rodrigo; Costa, Edwina Santos da; Moraes, Aline Vargas de; Ruiz, Cleudinéia Santos Domingos; Gomes, Iverson Morais (Ra'e Ga: o Espaço Geográfico em Análise, 2025)
The annual analysis of land use and fire hotspots is crucial for wildfire prevention and control strategies, providing key indicators of environmental impact. Several studies highlighted fire as a fundamental element in shaping the landscapes of the Cerrado, but frequent fires, combined with intensified land use, lead to a biodiversity loss. Land use and land cover data from MapBiomas were compiled, and fire hotspots from BDQueimadas were analyzed using QGIS and the R programming language. Although both land use/land cover (LULC) changes occur to a lesser extent, they are present throughout the municipality of Miranda, with more pronounced shifts in the NW. This region presents transitions from pasture to soybean plantations and other crops, along with a reduction in wetland areas. Regarding fire hotspots, the Pantanal biome recorded the highest numbers, with annual fluctuations influenced by both climatic and human factors. Fire hotspots were also observed in Indigenous lands, areas of the Serra da Bodoquena, the vicinity of the Pantanal do Rio Negro State Park Conservation Unit, and the SW portion of Miranda municipality. The analysis of fire hotspots reveals fire patterns and supports strategic planning to mitigate risks. The GIS software used provided effective visual analyses, essential to understand fire hotspot behavior and land use dynamics in Miranda, Mato Grosso do Sul State (MS).